Innovation for development and poverty reduction: an integrative literature review. Issue 1 (13th February 2017) - Pansera, Mario; Martinez, Fabien
Abstract : Purpose: The purpose of this paper is to develop a critical analysis of the innovation discourse, arguing that a more contextualised understanding of the challenges of innovation for development and poverty reduction in low-income economies will help the authors' to unravel new development opportunities and provide alternatives to conventional capitalist paths to innovation. Design/methodology/approach: The authors offer an integrative review of the literature addressing the topic of innovation emerging from within developing countries. Because existing innovation models are generally presented in ways that reflect practices and thought patterns inherent to the industrialised world, a literature review that offers an initial conceptualisation and synthesis of the literature to date on the theme of innovation from within developing countries provides for a more valuable contribution than a reconceptualization of existing models. Findings: The paper highlights different narratives of innovation, how they emerge and what are their implications. The authors outline a research agenda for generating new knowledge about innovation capabilities in what is generally known as the developing world. Originality/value: This paper shows that the recent evolution of the discourse of development is increasingly intertwined with elements that originated in other discursive worlds. The last three decades of innovation research have been characterised by a "cross-pollination" between different disciplines: development studies, science and technology studies, business management and organisation studies. By reviewing major research works conducted by scholars in these disciplines, this paper weds literature that heretofore have remained largely isolated from each other. The key innovation narratives that the study unveils – e.g. inclusive growth, bottom of the pyramid, grassroots innovation – address major questions of concern to these academic scholars around the political and socio-technical aspects that influence a firm's capacity to innovate in the context of developing countries.